Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

Engineering Chlorella-based consortia for sustainable food wastewater treatment: nutrient recovery, pollutant degradation and advanced harvesting - Lin Zhao; Shujie Wei; Yifan Zhang; Luguang Tao; Yuwei Xu; Yiming Wang; Zhangli Hu; Jun Tang; Song Wang (Environmental Research, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Spatial distribution, thickness characteristics, and environmental controls on soil organic carbon stocks of the mattic layer across the Qinghai-Tibetan Plateau - Jun Gu; Ming-Liang Ye; Fei Yang; Xiao-Dong Song; Alla Yurova; Gan-Lin Zhang (CATENA, 2026)

A novel benefit-oriented multi-objective optimization framework for efficiency, NOx, and H2S in coal-fired boilers - Cong Wang; Yiqing Yang; Bowen Lin; Jiaqi Ma; Jun Xu; Kai Xu; Long Jiang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Analysis of the deterioration rule and perception mechanism of egg yolk powder odor based on volatile omics, molecular docking and molecular dynamics simulation - Jiahui Song; Enhui Ma; Renrui Zheng; Zhuohang Huang; Jun Jiang; Zhijie Bao; Songyi Lin (Food Research International, 2026)

Low-molecular-weight lignin-mediated fabrication of ultra-thin, curved Bi4O5Br2/Co-TA Z-scheme heterojunctions for the photocatalytic degradation of styrene - Zhihu Ma; Xiaoming Song; Xueying Lu; Yixia Ren; Dezong Zheng; Lin Li; Jun Shen (Chemical Engineering Journal, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Reannotation of the ABCC transporters reveals a miR-980-BdABCC1 regulatory axis driving avermectin tolerance in Bactrocera dorsalis - Hou-Ji Song; Lin Wang; Wei Zhao; Guy Smagghe; Jin-Jun Wang; Dan-Dan Wei (Insect Biochemistry and Molecular Biology, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

ROS-responsive “Trojan Horse” nanoplatform via homotypic fibroblast-membrane camouflage for precision reprogramming of pathogenic synoviocytes in rheumatoid arthritis - Hua-Zhong Ying; Zhen-Hua Ying; Zhi-Min Rao; Song-Lin Jiang; Song-Zhao Zhang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Chen-Huan Yu (Chemical Engineering Journal, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Neuronal and Glial YAP/TAZ in the Spinal Cord Contribute to the Development of Bone Cancer Pain in Mice - Bo Peng; Xiaqing Lin; Jiang-Jian Hu; Huabao Liao; Cheng Li; Zhaoyu Li; Xue-Jun Song (Neuroscience Bulletin, 2026)

Non-Equilibrium Recovery of Plankton Communities in the Yangtze River Estuary: Three Years After the Fishing Ban - Bangping Deng; Wei Liu; Qiliang Song; Yuchen Guo; Chenxing Yang; Lin Zhu; Jun Li; Lijia Liu; Yin Yang; Xiucheng Yu (Fishes, 2026)
Large-scale fishing bans are increasingly implemented to restore aquatic ecosystems, yet their effects on lower trophic levels remain poorly understood. As one of the world’s largest estuarine systems, the Yangtze River Estuary has been subjected to a ten-year fishing ban since 2021, providing a unique opportunity to potentially examine the response of plankton community to reduced fishing pressure along a steep salinity–nutrient gradient. This study relies on one-off environmental and plankton field surveys conducted in autumn 2024 (a sampling instead of multi-year time-series monitoring), we applied redundancy analysis, Mantel tests, and threshold indicator taxa analysis to tentatively clarify the roles of nutrients and salinity in structuring post-ban plankton communities. Species richness may have increased substantially compared with pre-ban levels, but community evenness declined and the dominance of Skeletonema costatum could have intensified, revealing a possible non-equilibrium recovery pattern. Zooplankton density increased substantially, which may not be fully consistent with the expectation under a simple top-down release scenario. Threshold analysis showed that S. costatum exhibited bidirectional responses to dissolved inorganic nitrogen and phosphate, with its positive response thresholds matching ambient nutrient concentrations in the inner estuary; this discrepancy is only a plausible inference since we lack direct measurements of fish predation and zooplankton grazing rates to verify causal trophic interactions. Our findings suggest that bottom-up forces driven by persistent eutrophication remain the dominant control on plankton community structure three years after the ban. From a watershed management perspective, our observational results provide a tentative implication that substantial reductions in nutrient loading might be required to mitigate unbalanced plankton community recovery; otherwise, the structural integrity of plankton assemblages could lag far behind the recovery of species richness under the current eutrophic background.

Facile fabrication of PTFE/PET composite membrane with reinforced hydrophilic and antifouling properties for sustainable decentralized water system purification - Ludi Song; Yujie Fang; Xin Chen; Ziyuan Zhou; Liping Chen; Jun Yang; Ying Li; Yaqin Wu; Haitao Zhu; Lin Zhang; Congjie Gao (Journal of Environmental Management, 2026)

Nonlinear unsaturated seepage analysis via Picard iteration and level-set method within the scaled boundary finite element framework - Chuhao Huang; Jun Liu; Lei Gan; Wenbin Ye; Peiqing Wang; Xinwei Song; Gao Lin; Zhi liu (Computers and Geotechnics, 2026)

Sonar-Based Seepage Detection and Hydro-Thermal Modelling of Frozen Soil Curtain Evolution for Subway Cross-Passages in High-Permeability Strata - Shengbin Hu; Hang Lin; Jun Hu; Bafeng Ren; Xiaofeng Song; Zhuang Hu; Hanyu Dang (Geotechnical and Geological Engineering, 2026)

Transfer learning model for coal lower heating value prediction with improved applicability to cross-sample datasets - Jiaqi Ma; Jun Xu; Cong Wang; Bowen Lin; Long Jiang; Kai Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (International Journal of Coal Geology, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Bandgap-engineered iron-coordinated quercetin for enhanced visible-light photodynamic inactivation and strawberry preservation - Kaiyuan Su; Haoqian Chen; Zhuoran Guo; Yikai Song; Lin Yang; Jun Liu; Jianlong Wang; Wentao Zhang; Shuo Shi (Food Bioscience, 2026)

Ferroelectric field gating-assisted thermoelectric energy conversion - Ji Young Park; Sun-Woo Kim; Byoungjin Yoon; Youngbo Shim; Do-Heon Kim; Seong Wook Cho; Jun Chen; Young Hun Jeong; Sangwoo Ryu; Hak Ki Yu; Zhong Lin Wang; Hyesung Park; et al. (Chemical Engineering Journal, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Isolation and biological evaluation of a novel steroid from Sagina japonica (Sw. ex Steud.) Ohwi - Jun-Hong Liu; Qian-Lian Yin; Xue Li; Mei Qing Zhang; Lin Guo Zou; Xin Jian Song; Li Jiang; Chun Hua Liu; Yong Jun Li (Natural Product Research, 2026)

Cometabolic defluorination of two poly-fluoroalkyl substances by a new Sphingopyxis isolate - Zhaozhao Gao; Xingjia Xiang; Meng Yan; Yongqi Liu; Yucheng Wu; Xin Song; Xiangui Lin; Frank E. Löffler; Jun Zeng (Water Research, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Insight into the internal microscopic structure and composition of aerobic granular sludge under high salinity based on high-resolution Micro-CT technology - Yuhao Tong; Aqiang Ding; Jun Liu; Lin Quan; Hao Liu; Fuzhong Song; Demin Yang; Daijun Zhang; Peili Lu (Environmental Research, 2026)

A new fucosylated glucuronoxylomannan from the fruit bodies of Tremella aurantia: structural characterization and immunoenhancing activity on seasonal influenza mRNA vaccine - Jing Chen; Yuan Ma; Zhi-Min Rao; Song-Lin Jiang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2026)

Analysis of the mechanism of quality deterioration of egg yolk powder during storage from a multi-dimensional perspective - Yiding Yu; Jiahui Song; Jun Jiang; Songyi Lin (Food Chemistry, 2025)

Interplay of plasma-treated BiVO4 photoanode and CoFe metal organic frameworks enabled synergistic photoelectrochemical water splitting - Zhi-Cheng Yan; Min-Ho Lin; Chen-Hao Yeh; Pei-Lun Chen; Jun Song Chen; Po-Hsuan Hsiao; Chia-Yun Chen (Chemical Engineering Journal, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Ratiometric photoelectrochemical aptasensor for ultrasensitive kanamycin detection based on superior photoactive high-entropy sulfide nanosheets coupling with dual-atom nanozyme inducing polarity switch - Jia-Lin Li; Li-Ping Mei; Ai-Jun Wang; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Establishment and application of environmental geochemical baseline of soil PTEs in a typical metal mining area: a case study of the Xinqiao mining area in Tongling city, Anhui province, China - Jun Zhang; Manli Lin; Herong Gui; Song Chen; Xianghong Liu; Meiping Wu; Xinrui Huang; Li Ma; Weihua Peng (Journal of Soils and Sediments, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

A comprehensive atlas of multi-tissue metabolome and microbiome shifts: Exploring obesity and insulin resistance induced by perinatal bisphenol S exposure in high-fat diet-fed offspring - Shuyin Li; Longhua Gao; Haoyue Song; Jiayi Lin; Shen Zhang; Philippe Schmitt-Kopplin; Jun Zeng (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Mineral, molecular composition and ecosystem type jointly determine the stability of soil organic carbon on the Qinghai-Tibetan Plateau - Jun Gu; Dongxue Li; Fei Yang; Xiao-Dong Song; Ke-Yang Gong; Gan-Lin Zhang (CATENA, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

Synergy between single atom and nanoclusters promotes power and CO tolerant performance in PEMFCs - Jiwen Lin; Zhongyao Zhang; Jiaye Qiu; Yujie Wu; Jun Yu; Yongliang Li; Xiangzhong Ren; Lei Zhang; Zhongxin Song (Chemical Engineering Journal, 2025)

Judicious inhibition of interfacial non-radiative recombination via chlorine-isomerized self-assembled molecules for efficient and durable organic solar cells - Hao Xu; Xingting Liu; Shanlei Xu; Kin-Long Wong; Xinjie Zhou; Huilong Chen; Yijin Lin; Renyong Geng; Weiguo Zhu; Jun Yin; Xin Song (Chemical Engineering Journal, 2025)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Polycyclic aromatic hydrocarbons emissions from biomass-fueled boilers in China - Chunlin Zhang; Meixue Yang; Jiangyong Li; Hao Wang; Lin Song; Liran Shen; Li Bai; Yujun Lin; Jun Liu; Boguang Wang (Journal of Hazardous Materials, 2024)

A comprehensive evaluation of lightning location accuracy using a weighted gridding method - Lin Song; Qingda Li; Jun Yang; Qilin Zhang; Jie Li; Shudong Wang; Yuqing Zhong; Zhiren Zhou; Meng Zheng (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Deep nitrate accumulation in typical black soil critical zones of Northeast China - Shunhua Yang; Yue Dong; Mingyu Song; Jun Gu; Yonghui Shi; Huayong Wu; Xiaodong Song; Jinling Yang; Decheng Li; Gan-Lin Zhang (Science of The Total Environment, 2024)

Base on photothermal interfacial molecular transfer for efficient biodiesel catalysis via enzyme@cyclodextrin metal-organic frameworks loaded MXene - Qi Ao; Lin Jiang; Ying Song; Xinglai Tong; Tuohao Jiang; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2024)

Biochar regulates biogeochemical cycling of iron and chromium in a soil-rice system by stimulating Geobacter and Clostridium - Min XU; Yang LIN; Jing MA; Lulu LONG; Chao CHEN; Gang YANG; Chun SONG; Jun WU; Xiaohong ZHANG; Peng GAO (Pedosphere, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Edaphic regulation of soil organic carbon fractions in the mattic layer across the Qinghai-Tibetan Plateau - Jun Gu; Fei Yang; XiaoDong Song; ShunHua Yang; Gan-Lin Zhang (Science of The Total Environment, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Pre-deposited biochar enhanced flux stabilization and pollutant removal in gravity-driven membrane system - Caihong Liu; Qingyang Zuo; Jingjun Bo; Haiqing Chang; Lin Li; Qiang He; Dan Song; Jun Ma (Chemical Engineering Journal, 2024)

Phosphorus and selenium compounding mitigates Cr stress in peanut seedlings by enhancing growth homeostasis and antioxidant properties - Hongliang Yin; Yongping Jing; Yunqing Lin; Ningning Song; Haiying Zong; Fangli Wang; Shaojing Li; Xin Song; Hong Hou; Yuxian Shang Guan; Quanli Zong; Jun Liu (Environmental Science and Pollution Research, 2024)

Enhancing extracellular monascus pigment production in submerged fermentation with engineered microbial consortia - Song Zhang; Meng Shu; Zihan Gong; Xinyi Liu; Chenyu Zhang; Ying Liang; Qinlu Lin; Bo Zhou; Ting Guo; Jun Liu (Food Microbiology, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

Association Between Prenatal Per- and Polyfluoroalkyl Substance Exposure and Maternal Serum Total Bile Acid Levels During Pregnancy: Effect Modification by Infant Sex and Maternal Prepregnancy BMI - Qian Liao; Huishen Huang; Peng Tang; Jun Liang; Jiehua Chen; Lei Lei; Yanye Song; Dongxiang Pan; Mengrui Lin; Fangfang Lv; Xue Liang; Xiaoyun Zeng; et al. (Exposure and Health, 2024)

Shewanella oneidensis-based artificial conductive micro-niche for hydrogen augmentation - Song Lin; Tailin Wang; Zhengyu Tao; Zhenhui Li; Shangsong Li; Xiaoman Liu; Jun Liu; Xin Huang (Chemical Engineering Journal, 2024)

A vertical-flow constructed wetland–microalgal membrane photobioreactor integrated system for treating high-pollution-load marine aquaculture wastewater: A lab-scale study - Lin Zhao; Jun Tang; Yuwei Xu; Yifan Zhang; Zihao Song; Guiping Fu; Zhangli Hu (Science of The Total Environment, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Multifunctional phosphorus-containing imidazoliums endowing one-component epoxy resins with superior thermal latency, heat resistance, mechanical properties, and fire safety - Jingsheng Wang; Jun Wang; Shuang Yang; Xi Chen; Kaiwen Chen; Gen Zhou; Xian Liu; Lin Xu; Siqi Huo; Pingan Song; Hao Wang (Chemical Engineering Journal, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Preparation of CPVC-based activated carbon spheres and insight into the adsorption-desorption performance for typical volatile organic compounds - Ning Dong; Ze Wang; Jun Wang; Wenli Song; Lin Du; Xiangyu Gu; Songgeng Li (Environmental Pollution, 2024)

Modulating surface zinc species via facet engineering for efficient electroreduction of CO2 to CO - Junjie Wang; Zhaozhao Zhu; Yingxi Lin; Xueqiang Qi; Zhao Li; Jinxia Jiang; Xiaobin Niu; Jun Song Chen; Rui Wu (Chemical Engineering Journal, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

Core taxa, co-occurrence pattern, diversity, and metabolic pathways contributing to robust anaerobic biodegradation of chlorophenol - Ming Lin; Chenhui Pan; Chenyi Qian; Fei Tang; Siwen Zhao; Jun Guo; Yongming Zhang; Jiaxiu Song; Bruce E. Rittmann (Environmental Research, 2024)

Experimental and numerical investigation of the expansion mechanism of beam-end expansion devices in large-span bridge - Tao Liao; Juan Song; Jun Lai; Kai Wang; Ping Wang; Zhiheng Li; Jingmang Xu; Yao Qian; Junke Lin (Engineering Structures, 2024)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Construction of molecular enrichment accelerators via assembly of enzyme surface grafted polymer and cyclodextrin achieving rapid and stable ester catalysis for biodiesel synthesis - Qi Ao; Lin Jiang; Xinglai Tong; Ying Song; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Interaction of derivatives of cellulose and lignin in co-HTC, co-pyrolysis and co-activation - Jingyi Liang; Haisheng Lin; Chao Li; Lijun Zhang; Shu Zhang; Shuang Wang; Jun Xiang; Song Hu; Yi Wang; Xun Hu (Fuel, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

Low-temperature thermally enhanced bioremediation of polycyclic aromatic hydrocarbon-contaminated soil: Effects on fate, toxicity and bacterial communities - Jun Zeng; Ruini Wu; Tingting Peng; Qigang Li; Qing Wang; Yucheng Wu; Xin Song; Xiangui Lin (Environmental Pollution, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Corrigendum to “Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China” [Chemosphere. Dec 2022 309:136798] - Qian Liao; Peng Tang; Dongxiang Pan; Yanye Song; Lei Lei; Jun Liang; Bihu Liu; Mengrui Lin; Huishen Huang; Meile Mo; Chengtuo Huang; Ming Wei; et al. (Chemosphere, 2023)

Scour effects on the vertical dynamic response of single piles in transversely isotropic soils - Chun Lin Liu; Zhi Yong Ai; Meng Xiong Tang; He Song Hu; Lu Jun Wang (Ocean Engineering, 2023)

Intestine epithelial cell-derived extracellular vesicles alleviate inflammation induced by Clostridioides difficile TcdB through the activity of TGF-β1 - Shuangshuang Wan; Guangzhong Song; Hui Hu; Yaqing Xu; Peng Zeng; Shan Lin; Jun Yang; Jinqin Jiang; Xiaojun Song; Yongneng Luo; Dazhi Jin (Molecular & Cellular Toxicology, 2023)
Background Clostridioides difficile infection (CDI) has been primarily associated with the toxin B (TcdB), one of the three known protein toxins secreted by C. difficile , which can activate the intestinal immune system and lead to pathological damage. Even though the biological functions of intestine epithelial cell-derived extracellular vesicles (I-Evs) have been well documented, the role of I-Evs in the process of CDI is still unknown. Objectives The protective effect of I-Evs against C. difficile TcdB was investigated both in cultured murine colon carcinoma MC38 cells and a mouse model used in this study. Results Mouse I-Evs with mean diameter ranging from 100 to 200 nm and a density of 1.09–1.17 g/mL were obtained and confirmed containing the Ev-associated specific surface markers CD63 and TSG101 as well as high level of TGF-β1. In MC38 cells, I-Evs were able to decrease the gene expression of IL-6, TNF-α, IL-1β, and IL-22 induced by C. difficile TcdB, but to increase both the gene expression and protein levels of TGF-β1. I-Evs treatment via intraperitoneal administration alleviates C. difficile TcdB-induced local colon inflammation in mice and increased their survival rate from 50% up to 80%. Furthermore, I-Evs induced an increase in the proportion of CD4 + Foxp3 + Tregs in vitro and in vivo through a TGF-β1-dependent mechanism by activating the TGF-β1 pathway and prompting phosphorylation of the downstream proteins Smad 2/3. Conclusion For the first time, our study demonstrated that I-Evs originated from intestine epithelial cells can alleviate inflammation induced by C. difficile TcdB both in vitro and in vivo. Therefore, I-Evs might be potentially a novel endogenous candidate for effective treatment of CDI.

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Cartilage-targeting mRNA-lipid nanoparticles rescue perifocal apoptotic chondrocytes for integrative cartilage repair - Xinning Yu; Tengjing Xu; Huimin Shi; Jianqiao Hong; Xiaoqiang Jin; Le Cao; Jiajie Wang; Yunting Lin; Zongyou Pan; Siheng Wang; Jinghua Fang; Kaiwang Xu; et al. (Chemical Engineering Journal, 2023)

Linking peptide-oriented surface imprinting magnetic nanoparticle with carbon nanotube-based fluorescence signal output device for ultrasensitive detection of glycoprotein - Shi-Song Yu; Yu-Jun Shi; Di Wang; Ti-Ti Qiang; Ya-Qi Zhao; Xin-Yu Wang; Jia-Meng Zhao; Lin-Yi Dong; Ya-Jie Huang; Xian-Hua Wang (Analytica Chimica Acta, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Dielectric barrier discharge plasma for the remediation of microplastic-contaminated soil from landfill - Jingyuan Sima; Jun Wang; Jiaxing Song; Xudong Du; Fangfang Lou; Yuhan Pan; Qunxing Huang; Chengqian Lin; Qin Wang; Guangjie Zhao (Chemosphere, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Application of the Gini Index on the Evaluation of the Environmental Heterogeneity and Habitat Suitability Index for Larval Gobies - Lu Zhai; Rong Wan; Siquan Tian; Zengguang Li; Pengbo Song; Jun Lin (Journal of Marine Science and Engineering, 2023)
Spatial environmental heterogeneity in the Yangtze River Estuary (YRE) is always mentioned but rarely quantified and included in the evaluation process. This study introduced the habitat suitability index evaluation model based on the Gini index (HSIgini) to evaluate the optimal ranges of suitable environmental factors for three typical estuarine gobies, i.e., Rhinogobius giurinus, Acentrogobius pflaumii, Odontamblyopus rubicundus, and their habitat quality. The evaluation was carried out based on field surveys conducted in the spring and summer of 2018–2020. The Lorentz curve and Gini index were used to evaluate the spatial environmental heterogeneities in the YRE. The spatial heterogeneity of environmental factors in the Yangtze Estuary ranged from 0.62 to 0.05, with the highest Gini index for salinity and the lowest for temperature. The combination of environmental factors had significant spatial effects on habitat, with temperature showing mainly seasonal effects. The study indicated that the YRE is a good habitat for gobies and that there is spatial and seasonal differentiation in the habitats of different species, greatly reducing interspecific competition. Environmental heterogeneity is important for biological processes and should be incorporated into the modeling of bio–environmental relationships in future research to provide a basis for environmental and biological conservation and management.

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Rapid and sensitive detection of quizalofop-p-ethyl by gold nanoparticle-based lateral flow immunoassay in agriproducts and environmental samples - Xue Liu; Jiao Li; Yue Huang; Zhongrong Zhang; Qing Lin; Pengliang Xia; Fanyu Kong; Jun Qiu; Song Fang; Xiude Hua (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Cluster analysis of the domain of microseismic event attributes for floor water inrush warning in the working face - Guo-Jun Shang; Xiao-Fei Liu; Li Li; Li-Song Zhao; Jin-Song Shen; Wei-Lin Huang (Applied Geophysics, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Effects of Microplastics on Microbial Community in Zhanjiang Mangrove Sediments - Meng-Meng Chen; Fang-Hong Nie; Aftab Qamar; Di-hua Zhu; Yao Hu; Min Zhang; Qing-Lang Song; Hong-Ying Lin; Zhi-Bao Chen; Su-Qing Liu; Jin-Jun Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Upregulation of h-TERT and Ki-67 in ectopic endometrium is associated with recurrence of endometriosis - Jie Luo; Zhimin Song; Tao Zhang; Ketan Chu; Jingyi Li; Jianhong Zhou; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Effect of replacing inorganic trace minerals at lower organic levels on growth performance, blood parameters, antioxidant status, immune indexes, and fecal mineral excretion in weaned piglets - Wen-Fei Zhang; Min Tian; Jun-Shuai Song; Fang Chen; Gang Lin; Shi-Hai Zhang; Wu-Tai Guan (Tropical Animal Health and Production, 2021)

The involvement of α‐proteobacteria Phenylobacterium in maintaining the dominance of toxic Microcystis blooms in Lake Taihu, China - Jun Zuo; Lili Hu; Wei Shen; Jiaying Zeng; Lin Li; Lirong Song; Nanqin Gan (Environmental Microbiology, 2021)
Summary Lake Taihu in China has suffered serious harmful cyanobacterial blooms for decades. The algal blooms threaten the ecological sustainability, drinking water safety, and human health. Although the roles of abiotic factors (such as water temperature and nutrient loading) in promoting Microcystis blooms have been well studied, the importance of biotic factors (e.g. bacterial community) in promoting and meditating Microcystis blooms remains unclear. In this study, we investigated the ecological dynamics of bacterial community, the ratio of toxic Microcystis , as well as microcystin in Lake Taihu. High‐throughput 16S rRNA sequencing and principal component analysis (PCA) revealed that the bacteria community compositions (BCCs) clustered into three groups, the partitioning of which corresponded to that of groups according to the toxic profiles (the ratio of toxic Microcystis to total Microcystis , and the microcystin concentrations) of the samples. Further Spearman's correlation network showed that the α‐proteobacteria Phenylobacterium strongly positively correlated with the toxic profiles. Subsequent laboratory chemostats experiments demonstrated that three Phenylobacterium strains promoted the dominance of the toxic Microcystis aeruginosa PCC7806 when co‐culturing with the non‐toxic PCC7806 mcyB − mutant. Taken together, our data suggested that the α‐proteobacteria Phenylobacterium may play a vital role in the maintenance of toxic Microcystis dominance in Lake Taihu.

Identification of 5S and 45S rDNA sites in Chrysanthemum species by using oligonucleotide fluorescence in situ hybridization (Oligo-FISH) - Jun He; Sisi Lin; Zhongyu Yu; Aiping Song; Zhiyong Guan; Weimin Fang; Sumei Chen; Fei Zhang; Jiafu Jiang; Fadi Chen; Haibin Wang (Molecular Biology Reports, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Two new sesquiterpenoid glycosides from the stems of Zanthoxylum armatum DC - Ya-Lin Liu; Liang-Liang Gao; Tong-Tong Song; Tao Guo; Jun Chang (Natural Product Research, 2020)

New insight into the molecular phylogeny of the genus Liparis s.l. (Orchidaceae: Malaxideae) with a new generic segregate: Blepharoglossum - Lin Li; Shih-Wen Chung; Bo Li; Song-Jun Zeng; Hai-Fei Yan; Shi-Jin Li (Plant Systematics and Evolution, 2020)
Molecular studies have shown that Liparis s.l. is polyphyletic, with the epiphytic Liparis alliance well separated from the clade representing Liparis in its restricted sense and further forming a phylogenetically heterogeneous assemblage. The generic status of Cestichis , as the key member of the epiphytic Liparis alliance, remains contentious, and the relationships between Cestichis , Stichorkis and Platystyliparis are still unclear and in need of further studies. We herein employ DNA sequence data from nuclear ITS and plastid mat K regions to clarify the generic boundaries of Cestichis and its relationship to the allied genera. Results from both Bayesian inference and maximum likelihood analysis congruently indicate that Cestichis as currently circumscribed is not monophyletic. The Blepharoglossum clade, corresponding to commonly recognized sect. Blepharoglossum , forms a monophyletic lineage closely related to the genus Oberonia instead of the core Cestichis clade. A re-evaluation of the diagnostic morphological characters reveals that this lineage represents a morphologically distinct group. Based on these results, Blepharoglossum is removed from Cestichis and elevated to generic status. Our study also sheds light on the homoplastic nature of some diagnostic morphological characters used traditionally in the taxonomy of the Malaxidinae.

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

Pore Fractal Characteristics of Lignite at Different Temperatures Based on Mercury Intrusion Test - Yue Song; Jun Xie; Haizheng Fu; Lin Xin (Geotechnical and Geological Engineering, 2019)

SEM Image Analysis of Pore and Fracture Characteristics of Lignite Under Temperature Gradient - Yue Song; Jun Xie; Lin Xin; Haizheng Fu (Geotechnical and Geological Engineering, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Drift analysis of MH370 debris in the southern Indian Ocean - Jia Gao; Lin Mu; Xianwen Bao; Jun Song; Yang Ding (Frontiers of Earth Science, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Geochronology, geochemistry, Sr–Nd–Hf isotopic compositions, and petrogenetic and tectonic implications of Early Cretaceous intrusions associated with the Duolong porphyry–epithermal Cu–Au deposit, central Tibet - Shaogang Wei; Yang Song; Juxing Tang; Zhibo Liu; Qin Wang; Bin Lin; Jun Feng; Lin Hou; Wangxiu Danzhen (International Geology Review, 2018)

Effect of pad-fan cooling and dietary organic acid supplementation during late gestation and lactation on reproductive performance and antioxidant status of multiparous sows in hot weather - Jun Chen; Ji Guo; Wu-tai Guan; Jun-Jie Song; Zi-Xiao Deng; Lin Cheng; Yue-Lin Deng; Fang Chen; Shi-Hai Zhang; Yin-Zi Zhang; Fei Yang; Chun-Xiao Ren; et al. (Tropical Animal Health and Production, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Two new geranylphenylacetate glycosides from the barks of Cinnamomum cassia - Jun-Fen Zeng; Hu-Cheng Zhu; Jian-Wu Lu; Lin-Zhen Hu; Jin-Chun Song; Yong-Hui Zhang (Natural Product Research, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Iron supply prevents Cd uptake in Arabidopsis by inhibiting IRT1 expression and favoring competition between Fe and Cd uptake - Xiao Lin He; Shi Kan Fan; Jun Zhu; Mei Yan Guan; Xing Xing Liu; Yong Song Zhang; Chong Wei Jin (Plant and Soil, 2017)

Retraction Note to: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly(ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

RETRACTED ARTICLE: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly (ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

DNA Interaction, Photocleavage and Topoisomerase I Inhibition by Ru(II) Complex with a New Ligand Possessing Phenazine Unit - Xue-Wen Liu; You-Ming Shen; Jun-Shi Shu; Yang Xiao; Song-Bai Zhang; Ji-Lin Lu (Journal of Fluorescence, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Effects of catechins on Agrobacterium-mediated genetic transformation of Camellia sinensis - Da-Peng Song; Lin Feng; M. M. Rana; Ming-Jun Gao; Shu Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

G Protein-Coupled Estrogen Receptor–Protein Kinase A–ERK–CREB Signaling Pathway is Involved in the Regulation of Mouse Gubernaculum Testis Cells by Diethylstilbestrol - Xuan Zhang; Jian-hong Li; Shou-xing Duan; Qing-Jun Lin; Song Ke; Lian Ma; Tian-hua Huang; Xue-wu Jiang (Archives of Environmental Contamination and Toxicology, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

Biodegradation of high concentration of nitrobenzene by Pseudomonas corrugata embedded in peat-phosphate esterified polyvinyl alcohol - Na Liu; Hai-jun Li; Yue-e Shi; Bo-lin Zhu; Song Gao (World Journal of Microbiology and Biotechnology, 2013)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Nuclear and cytoplasmic genome components of Solanum tuberosum + S. chacoense somatic hybrids and three SSR alleles related to bacterial wilt resistance - Lin Chen; Xianpu Guo; Conghua Xie; Li He; Xingkui Cai; Lingli Tian; Botao Song; Jun Liu (Theoretical and Applied Genetics, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Chemistry, bioactivity and quality control of Dendrobium, a commonly used tonic herb in traditional Chinese medicine - Jun Xu; Quan-Bin Han; Song-Lin Li; Xiao-Jia Chen; Xiao-Ning Wang; Zhong-Zhen Zhao; Hu-Biao Chen (Phytochemistry Reviews, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

Influence of CYP2C19 loss-of-function variants on the antiplatelet effects and cardiovascular events in clopidogrel-treated Chinese patients undergoing percutaneous coronary intervention - Jian-Jun Zou; Hong-Guang Xie; Shao-Liang Chen; Jie Tan; Ling Lin; Ying-Ying Zhao; Hai-Mei Xu; Song Lin; Juan Zhang; Guang-Ji Wang (European Journal of Clinical Pharmacology, 2013)

A new isoform of thioredoxin h group in potato, SbTRXh1, regulates cold-induced sweetening of potato tubers by adjusting sucrose content - Tianjiu He; Botao Song; Jun Liu; Xia Chen; Yongbin Ou; Yuan Lin; Huiling Zhang; Conghua Xie (Plant Cell Reports, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Modulation of gene expression in cold-induced sweetening resistant potato species Solanum berthaultii exposed to low temperature - Xia Chen; Botao Song; Jun Liu; Jianwen Yang; Tianjiu He; Yuan Lin; Huiling Zhang; Conghua Xie (Molecular Genetics and Genomics, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Low-frequency variability of a semi-closed sea induced by the circulation in an adjacent ocean in a wind-driven, quasi-geostrophic, eddy-resolving simulation - Lin Mu; Linhao Zhong; Lijuan Hua; Jun Song (Ocean Dynamics, 2011)

Modulation of endogenous peroxidase by exogenous peroxidase in chinese red radish seedling - Li Wang; Lan Wang; Fang-Jun Li; Lin-Song Wang; Myeong-Hyeon Wang (Horticulture, Environment, and Biotechnology, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

Collateral vessel growth induced by femoral artery ligature is impaired by denervation - Ming-ying Luo; Bao-lin Yang; Feng Ye; Xiaoqiong Wu; Song Peng; Bin Yi; Wei Wang; Wu Zhu; Hua Luo; Jian-Guo Wen; Wei-Jun Cai; Jutta Schaper; et al. (Molecular and Cellular Biochemistry, 2011)

Molecular cloning, genomic structure and expression analysis of major histocompatibility complex class Iα gene of half-smooth tongue sole (Cynoglossus semilaevis) - Tian-jun Xu; Song-lin Chen (Fish Physiology and Biochemistry, 2011)

Cloning and characterization of a novel CONSTANS-like gene from Phalaenopsis hybrida - Jian-Xia Zhang; Kun-Lin Wu; Li-Ning Tian; Song-Jun Zeng; Jun Duan (Acta Physiologiae Plantarum, 2011)

Characterization of a male sterile mutant from progeny of a transgenic plant containing a leaf senescence-inhibition gene in wheat - Ya-Jun Xi; Xue-Feng Ma; Huan Zhong; Shu-Dong Liu; Zhu-Lin Wang; Yang-Yang Song; Cheng-Hui Zhao (Euphytica, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Allelic variation, balancing selection and positive selected sites detected from MHC class Iα gene of olive flounder - Tian-jun Xu; Yue-na Sun; Song-lin Chen (Genetica, 2010)

RNA interference against interleukin-5 attenuates airway inflammation and hyperresponsiveness in an asthma model - Shao-xing Chen; Feng-ying Huang; Guang-hong Tan; Cai-chun Wang; Yong-hao Huang; Hua Wang; Song-lin Zhou; Fan Chen; Ying-ying Lin; Jun-bao Liu (Journal of Zhejiang University-SCIENCE B, 2009)

Allelopathic Enhancement and Differential Gene Expression in Rice under Low Nitrogen Treatment - Biqing Song; Jun Xiong; Changxun Fang; Long Qiu; Riyu Lin; Yiyuan Liang; Wenxiong Lin (Journal of Chemical Ecology, 2008)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

Antioxidants and a new dihydroisocoumarins from Polygala hongkongensis Hemsl - Jian-Feng Wu; Si-Bao Chen; Jing-Chun Gao; Hao-Liang Song; Li-Jun Wu; Shi-lin Chen; Peng-Fei Tu (Natural Product Research, 2007)

A rice transcription factor OsbHLH1 is involved in cold stress response - Yu-Jun Wang; Zhi-Gang Zhang; Xin-Jian He; Hua-Lin Zhou; Yu-Xiang Wen; Ji-Xun Dai; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2003)